2015
DOI: 10.1093/cid/civ101
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Steatohepatitis and Hepatic Fibrosis in HIV-1–Monoinfected Adults With Elevated Aminotransferase Levels on Antiretroviral Therapy

Abstract: HIV-infected adults with chronic aminotransferase elevations while receiving ART have a high rate of liver disease. Noninvasive testing can help identify liver disease in such patients, but liver biopsy is necessary to definitively identify those at risk for liver disease progression and complications. Longitudinal follow-up of this cohort will better characterize the natural history of aminotransferase elevations in this population and identify noninvasive biomarkers of liver disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
2
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(107 citation statements)
references
References 42 publications
5
96
2
4
Order By: Relevance
“…In patients with Wilson disease, carriers of the mutant rs738409[G] allele had a higher prevalence of steatosis [49]. In HIV mono-infected patients, rs738409 [G] has been associated with steatosis, NASH, and fibrosis [50,51]. Finally, PNPLA3 has been shown to increase the risk of hepatic steatosis/fibrosis in individuals with inflammatory bowel diseases [52].…”
Section: Other Liver Diseasesmentioning
confidence: 99%
“…In patients with Wilson disease, carriers of the mutant rs738409[G] allele had a higher prevalence of steatosis [49]. In HIV mono-infected patients, rs738409 [G] has been associated with steatosis, NASH, and fibrosis [50,51]. Finally, PNPLA3 has been shown to increase the risk of hepatic steatosis/fibrosis in individuals with inflammatory bowel diseases [52].…”
Section: Other Liver Diseasesmentioning
confidence: 99%
“…Similarly, in a cohort of 225 HIV-mono-infected patients, 28 were classified as not having fibrosis on FIB-4 [23], while in another cohort of 62 patients FIB4 ≤1.45 and >3. 25 were found in 37 (59.7%) and 5 (8%) patients, respectively [22]. Conversely, a slightly higher prevalence of 8% of APRI values >1.5 was found in 432 HIV-mono-infected patients, and both diabetes and detectable HIV viremia were confirmed as risk factors for significant fibrosis [30].…”
Section: Discussionmentioning
confidence: 92%
“…Morse et al biopsied a cohort of 62 patients with similar features and found steatosis in 45 (73%), NASH in 34 (55%) and bridging fibrosis in 11 (17%) patients [22].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…review o ispanica come fattori di rischio nello sviluppo di NAFLD (1,6). La prevalenza di NAFLD nelle persone con infezione da HIV (PLHIV) su biopsie epatiche di pazienti con ipertransaminasemia è risultata elevata (>50%) con un'alta percentuale di NASH (7)(8)(9)(10)(11)(12). Considerando le diagnosi eseguite con metodiche diagnostiche non invasive (ecografia, fibroscan, TAC e risonanza magnetica) la prevalenza di NAFLD si aggira tra il 13% e il 58% nei diversi studi pubblicati (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Riassuntounclassified